ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA SEKOLAH DASAR PADA MATERI PECAHAN SISWA KELAS III - Ni Ketut Vira Indiani; I Made Sujana Adnyana (STKIP Subang, 2026)
This study aims to analyze the numeracy literacy skills of third-grade elementary school students on fractions and identify the factors that influence them. Numeracy literacy includes not only the ability to count, but also conceptual understanding, mathematical reasoning, and the ability to apply mathematics in everyday life contexts. This study used a qualitative descriptive approach with third-grade students in one elementary school as subjects. Data collection was carried out through written tests, interviews, and observations of the learning process. The test instrument was designed to measure understanding of fraction concepts, the ability to compare fractions, and contextual problem-solving skills. The results of the study indicate that students' numeracy literacy skills on fractions are still classified as low to moderate. Some students are able to recognize simple fractions, but do not yet understand the concept in depth, especially in terms of the relationship between the numerator and the denominator. Difficulties are also seen when students are asked to compare two fractions or solve story problems related to real situations. Common errors include inaccuracy in determining fraction values, errors in problem interpretation, and a lack of ability to relate mathematical concepts to everyday life. Factors influencing these conditions include teacher-centered learning methods, the lack of use of concrete learning media, and limited context-based practice questions. Furthermore, low student interest and motivation in learning also affect learning outcomes. Therefore, improvement efforts are needed through the implementation of more contextual, interactive, and problem-based learning. Teachers are expected to be able to create a learning environment that supports concept exploration so that students' numeracy literacy skills in fraction material can develop optimally and sustainably